Treatment of Severe Acetaminophen–Induced Hepatocellular Injury with Prostaglandin E: Two Case Reports - Marina Khatchatourian; Hillar Vellend (Canadian Journal of Gastroenterology)
Drugs have long been recognized as culprits in hepatocellular injury. Acetaminophen is one example of a commonly used over-the-counter medication that can cause severe centrolobular hepatic necrosis when ingested in large quantities in suicide attempts or unintentional overdoses. Acetaminophen hepatotoxicity is mediated by a toxic reactive metabolite formed from the parent compound by the cytochrome P450 mixed-function oxidase system of the hepatocyte. Conventional treatment of acetaminophen-induced liver injury consists of supportive measures and prevention of further drug absorption. In addition, in patients with high serum acetaminophen concentrations, the severity of hepatic necrosis appears to diminish with the timely use of sulfhydryl compounds such as N-acetyl cysteine. Two patients in whom acetaminophen hepatotoxicity was successfully treated using prostaglandin E1 are described.